Good occupation - bad occupation? The quality of apprenticeship training - Kathrin Goeggel; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Small average wage effects of employer and/or occupation changes mask large differences between occupation groups and apprentices with different schooling back-grounds. Apprentices in commerce and trading occupations strongly profit from an employer change. Employer and occupation changers in industrial occupations face large wage disadvantages however. We are the first to analyse these differences. Quality differences of apprenticeship quality between training firms that have been mainly discussed so far are small, however. This paper also explains differences between previous findings by comparing their estimation strategies. It demonstrates that selectivity into occupations and changers, unobserved heterogeneity between occupations, and the sample selection matter and proposes several improvements in the estimation technique to measure apprenticeship quality.
Keywords: J24; J31; M53; 330; Wage mark-up; apprenticeship training; occupations; Betriebliche Berufsausbildung; Qualifikation; Auszubildende; Lohnstruktur; Bildungsertrag; Deutschland